(untitled) (Medical Forum Monthly, 2024)
Objective: To describe hospital waste management plan in our setting for primary to tertiary hospitals and to make it environmental friendly with respect staff safety. Study Design: Observational / cross sectional study. Place and Duration of Study: This study was carried out at Bahawal Victoria Hospital, Bahawalpur from May to August 2015. Materials and Methods: This study carried out as an assignment for the course of Environmental and Occupational Health point of view. Data has been collected from the staff of the BV Hospital and the Quaid-e-Azam Medical College, Bahawalpur as our study subjects. The purpose of this paper is to outline the hospital waste management plan in our setting from primary to tertiary hospitals in a comprehensive way to put forward suggestions for further improvement. Results: Among the hospital staff particularly doctors were not aware of any hospital waste management protocol/plan. Similarly nobody form the hospital staff recalled any training program or such activity to be performed in their respective wards or departments since ever. Just the concerned nursing staff had sort of interaction with the sanitary workers and the sweepers engage in their routine hospital cleaning process supervised by the sanitary inspectors. As such no health facilities had properly implemented any hospital waste management plan in accordance to expected standard and practices; just routine maintenance of the hospital cleanliness is being carried out and the wastes were collected and moved to the point of transportation or being transported direct to its disposal point. Conclusion: There is need to develop Hospital Waste Management policy and plan for institutions along with its allocation of appropriate funds. Hosp Waste disposal standard operating procedures in a way that such model can be implemented anywhere by little modification as per need assessment basis in all of our healthcare settings.